An investigation into Linguistic features Of on-line chats In english and vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis attempts to investigate the grammatical features, commonly-used characteristics and paralinguistic cues of English and Vietnamese on-line chats. The data used in this study are collected from two popular chatrooms, one for Vietnamese chatters and the other for English chatters. The study is carried out through the adoption of descriptive, quantitative, qualitative and contrastive approaches. The findings of the research are compared and contrasted to reveal major similarities and differences in chatting between English and Vietnamese. This research also aims to help Vietnamese youths realize the problems of using chat language and its negative effects on the standard Vietnamese language. On the basis of the findings, some solutions to the problems of protecting and preserving the beauty and purity of the Vietnamese language are put forward.